Does coaches` satisfaction with the team determine their interpersonal style? The mediating role of basic psychological needs - Pulido, J. J.; López-Gajardo, M. A.; Ponce-Bordón, J. C.; Vaquero-Solís, M.; Leo, F. M. (European Journal of Sport Science, 2022)
The purpose of the present study was to examine how coaches` satisfaction with the team could be related to their reported interpersonal style towards young athletes, and to analyze the mediating role of basic psychological needs (i.e., need satisfaction and need frustration) in this relationship. Participants were 352 coaches (16-67 years old; Mage = 32.88, SD = 11.14) from 48 clubs, who had between 1 and 52 years of training experience (M = 23.23, SD = 15.02). Structural equation modeling (SEM) was employed to test the relationships between variables. Results showed that satisfaction with the team is positively related to coaches` need satisfaction, and negatively to their need frustration. Need satisfaction positively predicted coaches` need-supportive style, and need frustration predicted their need-thwarting style. Regarding indirect effects, need satisfaction positively mediated the relationship between coaches` satisfaction with the team and their need-supportive style, and need frustration negatively mediated the relationship between coaches` satisfaction with the team and their need-thwarting style. These findings are a first step to highlight satisfaction with the team as an antecedent of coaches` self-reported need-supportive and need-thwarting behaviors towards athletes, and the mediating role of coaches` psychological needs (need satisfaction and need frustration) in this relationship.